2015
DOI: 10.14778/2824032.2824078
|View full text |Cite
|
Sign up to set email alerts
|

Gorilla

Abstract: Large-scale internet services aim to remain highly available and responsive in the presence of unexpected failures. Providing this service often requires monitoring and analyzing tens of millions of measurements per second across a large number of systems, and one particularly effective solution is to store and query such measurements in a time series database (TSDB). A key challenge in the design of TSDBs is how to strike the right balance between efficiency, scalability, and reliability. In this pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(40 citation statements)
references
References 14 publications
0
38
0
2
Order By: Relevance
“…These measures are periodically sent to a central node, in charge of storing and analyzing them. We rely on a time-series database for this task, as they have proved to be an efficient tool to implement queries over moving sliding windows [26]- [28], such as the ones we use in our scheduling policy. Users submit their jobs by specifying the name of the container image (see Figure 2-).…”
Section: Architecturementioning
confidence: 99%
“…These measures are periodically sent to a central node, in charge of storing and analyzing them. We rely on a time-series database for this task, as they have proved to be an efficient tool to implement queries over moving sliding windows [26]- [28], such as the ones we use in our scheduling policy. Users submit their jobs by specifying the name of the container image (see Figure 2-).…”
Section: Architecturementioning
confidence: 99%
“…In addition to these three databases, the time series data base from Facebook Gorilla (Pelkonen et al, 2015) is also from high interest, because it is -a fast, scalable, In-Memory Time Series Database‖ (Pelkonen et al, 2015). Facebook uses this database to storage monitoring data from Facebooks-infrastructure for the past 26 hours and allows the automatic warning in case of anomalies and allows rapid searching of errors.…”
Section: Time Series Sensor Databasementioning
confidence: 99%
“…The database itself uses for persistent storage the data the Apache HBase database. (Pelkonen et al, 2015) To storage the time serious sensor data, each time series are identified by a unique key. This key is a string which is the only meta data.…”
Section: Time Series Sensor Databasementioning
confidence: 99%
See 2 more Smart Citations